MORPHO-SYNTACTIC ANALYSIS OF COMPOUND WORDS USED IN COVID-19 PANDEMIC REPORT BY WORLD HEALTH ORGANIZATION (WHO) - AHMADU , Mohammed Dauda (International Journal of Arts, Languages, Linguistics and Literary Studies, 2024)
This study examines the morpho-syntactic analysis of compound words used in COVID-19 pandemic report by World Health Organization (WHO). The study is limited to 2021 report from WHO which is purposively selected for data. The theoretical framework adopted for this research is a combination of Aranoff’s (1976) Word Based Approach to word formation rules and Beard’s (1995) Item and Arrangement Model. The study identified, analyzed, classified the most commonly used morpheme morphosyntactically. The data are elaborated based on their morphological contexts and in emphatic recurrence of such morphemes, the result shows that a word that can be morphologically and lexically categorized as a MORPHEME, but its internal composition may also show it as a GROUP. Also, such compound or acronymic morphemes contain certain semantic components that could be syntactically deciphered as clauses or sentences. Such acronymic compounds enable scientific report to capture lengthy or many messages in brief forms.